Генетические аспекты фотосинтеза ароматических сортов табакаи пути оптимизации селекции: урожай сухих листьев - Маркарян, В. А. (ՀԱԱՀ հիմնադրամ)
пятой статье серии обобщены результаты генетического анализа сортов табака Самсун по урожаю. Наследованию признака в F1 наиболее характерен промежуточный тип, детерминация и нарастание которого реализуется аддитивными генами с рецессивным характером, породившими отклонения между показателями урожая и эффектами общей комбинационной способности. Разработана новая тактика подбора перспективного исходного материала и отбора по совмещению в генотипах генов, контролирующих умеренный урожай и высокую ароматичность сырья. Շարքի հինգերորդ հոդվածում ամփոփված են ծխախոտի Սամսուն սորտերի բերքի գենետիկական անալիզի արդյունքները: F1 հիբրիդներին բնորոշ է հատկանիշի միջանկյալ ժառանգումը, որի դրսևորմանն ու աճին նպաստում են բերքի ցուցանիշների և ընդհանուր մակածական ունակության միջև շեղում առաջացնող ռեցեսիվ բնույթի ադիտիվ գեները: Մշակվել է գենոտիպում չափավոր բերքատվությունն ու հումքի բարձր բուրավետությունը վերահսկող գեների համատեղման ընտրության և հեռանկարային ելանյութերի ստացման նոր մոտեցում: The fifth article in the series summarizes the results of genetic analysis of 7 varieties of tobacco of the Samsun oriental variety type and their diallel hybrids for the yield of dry leaves. The trait inheritance in F1 is most characterized by an intermediate type, the determination and growth of which is realized primarily by additive genes with a recessive nature. These give rise to deviations between yield indicators and the effects of GCA. A new tactic has been developed for selecting promising starting materials and selecting for the combination of genes in genotypes that control moderate yield and high aromaticity of raw materials. For this purpose, the following varieties have been proposed: Samsun 47, Samsun 36, Samsun Bafra, and Samsun Maden, and universal hybrids Samsun 47xSamsun Bafra and Samsun 36xSamsun Bafra which are valuable both for heterosis and breeding. CMS analogues of maternal forms make it possible to organize hybrid seed production. Analyses of genetic correlations allow us to draw the most important conclusion about the reality of the combination in the genotypes of selected forms of moderate yield and high-quality raw materials by intensifying the photosynthetic apparatus. A new principle of selection in population has been developed: selection should be carried out according to the type of leaf of the aromatic variety Samsun Bafra, and to the rate of leaf formation-productive varieties Samsun 36 and Samsun 47.
Keywords: Агрономия и агроэкология